Switching adhesion and friction by light using photosensitive guest–host interactions. Issue 10 (18th December 2014) - Blass, Johanna; Bozna, Bianca L.; Albrecht, Marcel; Krings, Jennifer A.; Ravoo, Bart Jan; Wenz, Gerhard; Bennewitz, Roland
Abstract : Friction and adhesion between two β-cyclodextrin functionalized surfaces can be switched reversibly by external light stimuli. The interaction is mediated by complexation with ditopic azobenzene guest molecules. Abstract : Friction and adhesion between two β-cyclodextrin functionalized surfaces can be switched reversibly by external light stimuli. The interaction between the cyclodextrin molecules attached to the tip of an atomic force microscope and a silicon wafer surface is mediated by complexation of ditopic azobenzene guest molecules. At the single molecule level, the rupture force of an individual complex is 61 ± 10 pN.